Exploring the risk spillover effects among China's pilot carbon markets: A regular vine copula-CoES approach. (1st January 2020) - Zhu, Bangzhu; Zhou, Xinxing; Liu, Xianfeng; Wang, Haifang; He, Kaijian; Wang, Ping
Abstract: In this study, value at risk and conditional value at risk are used to measure the risks of pilot carbon markets of Beijing, Shanghai, Guangdong, Tianjin, Hubei, Shenzhen and Chongqing in China. Regular vine copula-CoES is used to measure the risk spillover effects among carbon markets of Guangdong, Hubei and Shenzhen with high transactions. The empirical results show that compared with the traditional value at risk, conditional value at risk can better measure the risks of carbon markets. Carbon markets of Chongqing, Tianjin and Shenzhen have higher risks than those of Hubei and Guangdong. Risk spillover effects are found between carbon markets of Guangdong and Shenzhen, rather than between those of Hubei and Guangdong. Highlights: Conditional value at risk are used to measure the risks of China's pilot carbon markets. Regular vine copula-CoES is used to measure the risk spillover effects between carbon markets of Guangdong, Hubei and Shenzhen. Conditional value at risk can better measure the risks of carbon markets than value at risk. Risk spillover effects are found between carbon markets of Guangdong and Shenzhen.